Undang-undang Islam Dalam Masyarakat Melayu: Analisis Terhadap Bentuk Pemikiran Dan Pandangan R.O. Winstedt - Abd Rahman, Mohd Farhan; Abd Rahim, Rahimin Affandi (Jurnal Fiqh, 2012)
This article will focus on R.O. Winstedt?s view concerning Islamic law in the Malay society, which emphasized more on the negative side rather than the positive side. In order to achieve such an objective, special attention is be given to the methodological approach used by Winstedt in the Islamic law. This article is divided into four sections. First, the introduction of the study; second, an evaluation of Winstedt?s methodological approach and thought followed by, third, an analysis of Winstedt?s point of view concerning Islamic law in the Malay Peninsula and finally the fourth, the conclusion and summary.